Les identités au travail : analyses et controverses - D'Amours, Martine (Relations industrielles / Industrial Relations, 2011)
The article reviews the book, "Les identités au travail: analyses et controverses," edited by Jean-Yves Causer, Jean-Pierre Durand and William Gasparini.
Keywords: Business And Economics--Labor And Industrial Relations; Business And Economics--Personnel Management; Labor Unions; SnR_publicationTitle_Relations Industrielles_Relations industrielles / Industrial Relations_2025-09-22T16:07:02.081Z